Ultra-broadband all-optical wavelength conversion in tellurite waveguides with engineered dispersion - Marconi, J. D.; Fagotto, E. A.M.; Abbade, M. L.F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2017)
An one-(1P) and a two-pump (2P) four-wave mixing ultra-broadband all-optical wavelength converter (AOWC), based on a tellurite waveguide, are proposed and numerically tested using 56 Gb/s QPSK signals. The 1P- and the 2P-AOWC provide wavelength conversion over a 5.5 and 12 THz band, respectively.